The Effects of Ketogenic Diet Treatment in Kcna1-Null Mouse, a Model of Sudden Unexpected Death in Epilepsy - Ren, Yandong; Chang, Jinlong; Li, Chengchong; Jia, Cuicui; Li, Ping; Wang, Yuhua; Chu, Xiang-Ping (Frontiers in Neurology, 2019)
Sudden unexpected death in epilepsy (SUDEP) is one of the most common causes of sudden death in patient with epilepsy. It accounts for 5% to 30% of all deaths in individuals with epilepsy. Ketogenic diet (KD), a dietary therapy for epilepsy, has been used in clinic during the past decade. However, the cellular and molecular mechanisms underlying the SUDEP and the relationship between KD and SUDEP are uncertain. Kcna1-null (Kcna1-/-) mouse, an animal model of SUDEP, is frequently used to study mechanisms underlying SUDEP. The current mini-review focus on risk factors for SUDEP and their relationship with KD treatment in Kcna1-/- mice. Emerging data suggest that factors including seizure frequency, longevity, rest, age and gender both in Kcna1-/- mice and KD treated Kcna1-/- mice are involved in SUDEP. This provides valuable prediction for clinical application of KD for treatment of SUDEP.